The clinical effectiveness and safety of intravenous unfractionated heparin following digital replantation and revascularization: A narrative systematic review. Issue 6 (12th May 2022) - Deblois, Simon; Zhu, Linda; Mastropasqua, Bruno; Thibaudeau, Stephanie; Ziegler, Daniela; Pomp, Alfons
Abstract: Background: Digital replants and revascularization (DRV) have been performed since the 1960s but there are no recognized standard peri‐operative anticoagulation practices. A narrative systematic review of the clinical effectiveness and safety of therapeutic peri‐operative unfractionated heparin following DRV was undertaken. Methods: A review of the literature from 1985 to March 2022 was conducted using Medline, Embase, CINAHL and EBM reviews. Unfractionated heparin (UFH) use following DRV was compared to low‐molecular weight heparin, other anticoagulants or no anticoagulation. Randomized trials, observational studies as well as guidelines were selected and independently screened. The Revised Cochrane risk‐of‐bias (RoB 2) tool and ROBINS‐I were used to appraise risk of bias. Results: While the search strategy identified 1490 references, only six studies met the inclusion criteria. Significant heterogeneity and the low methodological quality of the evidence precluded a meta‐analysis. Among the four studies that documented the surgical success rate associated with the use of a therapeutic dose of UFH post DRV, only two reported improved clinical outcomes. Evidence of a higher complication rate related to UFH use was found in four studies. Low quality evidence suggests that a therapeutic dose of unfractionated heparin leads to a higher risk of complications when compared with heparin given as an intermittent bolus of unfractionated heparin or subcutaneous heparin, or prostaglandin E1 or no heparin. Conclusions: Current evidence suggests that IV UFH use following DRV has no significant impact on the success of the intervention. Heparin use may not be innocuous as some studies showed increased bleeding complications.